Penggunaan biostimulan Orgamin untuk efisiensi pemupukan dan peningkatan produktivitas kelapa sawit di dataran tinggi Application of Orgamin biostimulan to enhance fertilizer efficiency and productivity of oil palm grown in highland - Happy WIDIASTUTI; Djoko SANTOSO; Soekarno Mismana PUTRA; Memed WIRAMIHARDJA; Aida FARIDA; B. MARAHIMIN MARAHIMIN; K. PANJAITAN PANJAITAN; Jisman SINAGA (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2013)
AbstractThe extension of oil palm area has been expanded tomarginal land such as the highland regions. However, theproductivity of the oil palm became the main demand for theplanters. Increasing of oil palm productivity can be done byapplication of growth regulators. Growth regulators aresmall molecules in a relatively very small amount that affectthe growth and development of plant. This study wasconducted to asses the efectiveness of plant growth regu-lators (Orgamin and Orgamin plus) in improving fertilizerefficiency and productivity of mature oil palm (TM 7). Theexperiments were conducted at Marjandi oil palm plantationat an altitude of 700 m above sea level in a total area of 16 ha. Six treatments tested were 1). 100% inorganicfertilizer (control), 2). 50% inorganic fertilizer + Orgamin(50K+O), 3). 75% inorganic fertilizer + Orgamin (75K+O),4). 50% inorganic fertilizer + Orgamin plus (50K+OP), 5).75% inorganic fertilizer + Orgamin plus (75K+OP), and 6).100% inorganic fertilizer + Orgamin plus (100K+OP)arranged in a randomized block design (RBD) with threereplications. Orgamin (O) and Orgamin plus (OP) wereapplied in the hole around the oil palm along with inorganicfertilizers. The results showed that application of O and OPimproved the efficiency of inorganic fertilizers by 50% basedon vegetative variables and increased the concentration ofN, P, and K of leaf and soil compared to those of 100%inorganic fertilizer. In addition to the height and leaf numberof plant parameters, the leaf of the plant treated with O andOP showed more greenish compared to those of control.There is an indication that the O application increased thepercentage of female flowers. In addition the application ofOrgamin also produced the highest oil content in oil palmfruit particularly in the treatment of 75% of inorganicfertilizer + orgamin harvested in October compared to thosein March. Moreover, application of OP increased both thetotal weight and weight per bunch of FFB.AbstrakPengembangan kelapa sawit mengharuskan pengguna-an lahan suboptimal seperti daerah dataran tinggi. Produk-tivitas kelapa sawit menjadi tuntutan utama bagi pekebun.Peningkatan produktivitas kelapa sawit di dataran tinggididuga dapat dilakukan dengan aplikasi zat pengatur tumbuh.Zat pengatur tumbuh merupakan molekul “kecil” (small molecules) yang dalam jumlah relatif sangat sedikit mem-pengaruhi pertumbuhan/perkembangan tanaman. Penelitiandilakukan untuk menguji formula zat pengatur tumbuh(Orgamin dan Orgamin plus) dalam meningkatkan efisiensipemupukan dan produktivitas kelapa sawit TM 7. Percobaandilakukan di kebun Marjandi dengan ketinggian 700 dpl padaareal seluas 16 ha. Enam perlakuan yang diuji adalah 1).pupuk anorganik 100% (100K), 2). pupuk anorganik 50% +Orgamin (50K+O), 3). pupuk anorganik 75% + Orgamin(75K+O), 4). pupuk anorganik 50% + Orgamin plus (50K+OP), 5). pupuk anorganik 75% + Orgamin plus (75K+OP),dan 6). pupuk anorganik 100% + Orgamin plus (100K+OP)yang disusun dalam rancangan acak kelompok (RAK)dengan tiga ulangan. Orgamin (O) dan Orgamin plus (OP)diberikan dalam lubang di piringan pokok bersamaan denganpupuk anorganik. Hasil pengamatan menunjukkan bahwapemberian O dan OP dapat meningkatkan efisiensi pemupuk-an anorganik hingga 50% dilihat dari beberapa peubahvegetatif dan menghasilkan kadar N, P, dan K daun dantanah lebih tinggi dibandingkan dengan pemberian pupukanorganik 100%. Selain pada parameter tinggi tanaman danjumlah daun, peningkatan juga terlihat pada tingkatkehijauan daun. Terdapat indikasi bahwa pemberian Orgaminmeningkatkan persentase jumlah bunga betina. PemberianOrgamin juga menghasilkan kadar minyak tertinggi khusus-nya pada pemberian Orgamin + pupuk anorganik 75% padabuah yang dipanen bulan Oktober dibandingkan dengan buahyang dipanen bulan Maret. Baik data bobot per tandanmaupun bobot TBS menunjukkan bahwa pemberian OPdapat meningkatkan kedua peubah tersebut.